Temporal stability of agricultural land-use effects on morphological traits and abundance in bumblebees and syrphid flies - Markus Birkenbach; Florian Straub; Nico Blüthgen; Jonas Kuppler; Lena Wilfert; Manfred Ayasse (Basic and Applied Ecology)
Pollinator populations are globally declining due to environmental and anthropogenic stressors, especially in agricultural areas. Land-use intensification and its consequences can shape both abundance and functional traits in pollinators, which may reduce pollination, and thus threaten ecosystem functioning. This study investigates temporal stability of land-use and climatic effects on morphological traits and abundance of the bumblebee Bombus lapidarius and the syrphid fly Episyrphus balteatus in agricultural grasslands. As responses, we measured body size and asymmetry using wing centroid sizes of specimen sampled in the years 2008, 2012 and 2020 and assessed the relative abundance of the two species. By using a variety of environmental variables on local and landscape-scale, reflecting land-use intensity and floral resource availability for pollinators, we were interested in the individual effects of the stressors, but particularly whether the effects are stable across the three sampling years. The body size of bumblebees decreased with local land-use intensity and increased with local availability of floral resources. In contrast the body size of syrphid flies decreased with landscape-level land-use and strongly depended on temperature. Bumblebee abundance declined with local land-use intensity, while syrphid flies were more abundant on plots with higher local land-use. The effects of most land-use stressors on both pollinator morphology and abundance showed consistent patterns across the three sampling years, except for local land-use and climatic factors, which showed significant interactive effects with the sampling year on the morphology of both species. Our results indicate that land-use effects on pollinators are stable over time and demonstrate that pollinators may be under persistent pressure of land-use in agricultural areas.